2018
DOI: 10.1016/j.jpeds.2017.12.048
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Outcome of Young Children with Biliary Atresia and Native Liver: Results from the ChiLDReN Study

Abstract: Clinicaltrials.gov: NCT00061828 and NCT00294684.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
2
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 30 publications
(36 reference statements)
4
55
2
7
Order By: Relevance
“…In a study conducted before the widespread availability of LT intervention, Stewart et al 1 reported that children with chronic LD scored lower than typically developing children of the same age on both IQ scores and physical variables -particularly height. Similarly, Ng et al 3 have reported poorer cognitive outcomes in children with biliary atresia, including an association between height measured at 18 months and a set of broad-based neurocognitive variables assessed longitudinally at 24 months. These data are consistent with our finding of the relationship between pre-transplant percentiles for height, and IQ measured at long-term follow-up.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In a study conducted before the widespread availability of LT intervention, Stewart et al 1 reported that children with chronic LD scored lower than typically developing children of the same age on both IQ scores and physical variables -particularly height. Similarly, Ng et al 3 have reported poorer cognitive outcomes in children with biliary atresia, including an association between height measured at 18 months and a set of broad-based neurocognitive variables assessed longitudinally at 24 months. These data are consistent with our finding of the relationship between pre-transplant percentiles for height, and IQ measured at long-term follow-up.…”
Section: Discussionmentioning
confidence: 87%
“…Chronic liver disease is associated with an array of negative symptoms 1,2 . Improvements in nutritional support, treatment delivery and access to liver transplantation (LT) has resulted in children with liver disease (LD) surviving illnesses that were normally fatal in infancy 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, several national and international BA research consortiums and registries have been set up to foster scientific progress with this rare condition (Table ). The relatively massive resources devoted to the ChiLDReN network in the USA is a good example of this, though one could argue that little novel has come of it, beyond consolidation of what was already known or at least inferred . The amazing discovery of biliatresone and its role in ovine BA owes more to insight and scientific perseverance than to a centrally‐directed research committee .…”
Section: Discussionmentioning
confidence: 99%
“…For cognition and executive functions, versions of the Wechsler Intelligence Scales (WISC) were the most used (15/17) (5,9,12,(14)(15)(16)(17)(18)(19)(20)(21)(22) . General, fine and gross motor development were assessed using the following instruments: Movement Assessment Battery for Children (M-ABC) (23) , Mullen Scales of Early Learning (MSEL) (10,24) , Bayley Development Scales (25,26) , Griffiths Mental Ability Scales (GMDS) (27) and General Development Scale of Minnesota Child Development Inventory (MCDI) (15) . Some of these instruments also evaluated general language (25) , receptive and expressive language (10,24) (TABLE 1).…”
Section: Study Characteristicsmentioning
confidence: 99%